PERAN STRATEGIS SEKTOR PERTANIAN, KEHUTANAN, DAN PERIKANAN SEBAGAI TULANG PUNGGUNG EKONOMI MASYARAKAT PERBATASAN: ANALISIS LITERATUR ATAS KONTRIBUSI DAN TANTANGAN PADA PERTUMBUHAN EKONOMI REGIONAL - Rita Hayati; Al-Amin (BORJUIS: JURNAL OF ECONOMY, 2025)
This study discusses the strategic role of the agriculture, forestry, and fisheries sectors as the backbone of the economy in border areas through a comprehensive literature analysis. These sectors make a major contribution to sustaining regional economic growth by providing employment, strengthening food security, supporting community income, and preserving the environment. However, optimising the role of these sectors still faces various challenges, such as limited infrastructure, restricted market access, low technology, socio-ecological conflicts, and policy and institutional challenges. The research method used systematic literature review with thematic analysis to identify contributions and obstacles faced. The research findings highlight the need for an integrated approach that strengthens infrastructure, human resource capacity, local institutions, and policy harmonisation to promote inclusive and sustainable regional economic growth in border areas. These findings are expected to serve as a basis for policy recommendations to strengthen the role of the agriculture, forestry, and fisheries sectors as drivers of the border community's economy.